PROSEDUR PENCEGAHAN DAN INTERVENSI PERILAKU SEKS BEBAS PADA REMAJA DALAM PERSPEKTIF PSIKOLOGI ISLAM: TINJAUAN STUDI LITERATUR - Putri Hidayati; Agung Perdana Putra; Khairunnas Rajab (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Free sexual behavior among adolescents is an increasingly alarming social problem with serious consequences for physical health, psychological well-being, and the moral fabric of society. Islamic psychology, as a discipline integrating modern psychological principles with Islamic values and epistemology, offers a unique analytical framework and distinctive intervention approach in understanding and addressing this problem. This study aims to systematically examine the causal factors, prevention procedures, and forms of intervention against free sexual behavior among adolescents from the perspective of Islamic psychology through a literature review method. Data were collected through documentation from national and international scientific journals, academic books, and relevant publications issued within the past ten years. Data analysis was conducted through content analysis and thematic analysis. The findings indicate that Islamic psychology understands free sexual behavior as a distortion of fitrah triggered by the weakening of the qalb, 'aql, and nafs al-lawwamah functions. Effective prevention rests on strengthening the internalization of tawhid values, character formation (akhlaq), and the role of family and Muslim community institutions. Recommended interventions include Islamic counseling, tazkiyatun nafs, spiritual guidance, and Islamic value-based programs proven effective in changing Muslim adolescents' attitudes and behaviors.